Differential Modulation of the Voltage-Gated Na+ Channel 1.6 by Peptides Derived From Fibroblast Growth Factor 14 - Singh, Aditya K.; Dvorak, Nolan M.; Tapia, Cynthia M.; Mosebarger, Angela; Ali, Syed R.; Bullock, Zaniqua; Chen, Haiying; Zhou, Jia; Laezza, Fernanda (Frontiers in Molecular Biosciences, 2021)
The voltage-gated Na+ (Nav) channel is a primary molecular determinant of the initiation and propagation of the action potential. Despite the central role of the pore-forming α subunit in conferring this functionality, protein:protein interactions (PPI) between the α subunit and auxiliary proteins are necessary for the full physiological activity of Nav channels. In the central nervous system (CNS), one such PPI occurs between the C-terminal domain of the Nav1.6 channel and fibroblast growth factor 14 (FGF14). Given the primacy of this PPI in regulating the excitability of neurons in clinically relevant brain regions, peptides targeting the FGF14:Nav1.6 PPI interface could be of pre-clinical value. In this work, we pharmacologically evaluated peptides derived from FGF14 that correspond to residues that are at FGF14’s PPI interface with the CTD of Nav1.6. These peptides, Pro-Leu-Glu-Val (PLEV) and Glu-Tyr-Tyr-Val (EYYV), which correspond to residues of the β12 sheet and β8-β9 loop of FGF14, respectively, were shown to inhibit FGF14:Nav1.6 complex assembly. In functional studies using whole-cell patch-clamp electrophysiology, PLEV and EYYV were shown to confer differential modulation of Nav1.6-mediated currents through mechanisms dependent upon the presence of FGF14. Crucially, these FGF14-dependent effects of PLEV and EYYV on Nav1.6-mediated currents were further shown to be dependent on the N-terminal domain of FGF14. Overall, these data suggest that the PLEV and EYYV peptides represent scaffolds to interrogate the Nav1.6 channel macromolecular complex in an effort to develop targeted pharmacological modulators.